Existence and Continuous Dependence for Fractional Partial Hyperbolic Differential Equations. (15th December 2015) - Dong, Qixiang; Wu, Guangxian; Zhu, Lanping
Abstract : This paper is concerned with a class of fractional hyperbolic partial differential equations with the Caputo derivative. Existence and continuous dependence results of solutions are obtained under the hypothesis of the Lipschitz condition without any restriction on the Lipschitz constant. Examples are discussed to illustrate the results.